Raspberry Pi OPAC - Mohd Nasir, Amar Izzat; Ahmad, Amal Harrith; Omar, Luqman; Zahimi, Zahimi; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2019)
Raspberry Pi is a credit card sized computer that has low power consumption, can connect to a TV or Monitor, uses a standard keyboard and mouse and runs a variety of Linux based operating systems known for easy customization.